Floating porous ceramics for high densiti cell culture in stirred bioreactors - Sopyan, Iis; Mel, Maizirwan; Fadli, Ahmad; Zulkifli, Nur Izzati (2010)
Floating porous ceramics has been successfully developed using protein foaming-consolidation method. This method allows the control of porosity not only by the varied concentration of protein but also by managing the foaming process. Slurries of alumina powders and yolk was prepared by stirring the mixture and the resulting slip was poured into cylindrical shaped molds. Subsequently, they were subjected to drying for foaming and/or consolidation. Foaming process condition determined mean pore size and pore distribution. The dried green bodies of the samples were then burned to remove the pore creating agent followed by sintering at 1550°C for 2 h. Pore size distribution measurement showed that macropores of the sintered alumina porous bodies increased with the increased time and temperature of the drying process and were found in the range 50 - 800 μm. SEM measurement also confirmed this observation. Less foamed samples show lower shrinkage but higher compressive strength. A shrinkage of as low as 7.8% was observed for the sample dried at 110ºC but it increased significantly to 29.3% when dried at 180ºC. The compressive strength of the 110ºC's sample was 5.72 MPa at 43.6% porosity and it decreased to 4.57 MPa at 50.4% porosity when foamed at 180ºC. Density varied from 0.9 to 1.5 g/cm3 depending on the preparation condition. These results have opened a novel preparative way for porous ceramics especially alumina-based porous materials designed for biomedical applications such as cell culture in stirred bioreactor, drug delivery, bone implant etc.